THE INTELLECTUAL TRADITION OF ABDUL QADIR AL-MANDILI IN THE HADITH BOOK OF TUHFAH AL-QARI' (RIWAYAH, 2025)
This study explores the intellectual legacy of a prominent Nusantara scholar, Abdul Qadir al-Mandili (1329–1385 AH / 1910–1965 CE), whose contributions to hadith studies are exemplified in his seminal work, Tuhfah al-Qāri’. This text represents a significant synthesis of traditional and contextual approaches to understanding hadith. The study seeks to examine the distinctive features of the work, its methodological framework, and its broader influence on the development of Islamic intellectual traditions in the Nusantara region. Employing content analysis and a historical approach, the research reveals that Tuhfah al-Qāri’ offers practical interpretative guidance for Muslims, aligning hadith comprehension with the socio-cultural realities of local communities. Furthermore, the work reflects the intellectual adaptability of Nusantara scholars who remained rooted in classical Islamic knowledge while engaging with the contemporary challenges of their era. The findings affirm that Tuhfah al-Qāri’ not only serves as a vital reference in the field of hadith studies but also functions as an intellectual bridge between global Islamic scholarship and local religious discourse, thereby enriching the dynamic continuity of Islamic thought in the region. [Penelitian ini mengkaji warisan intelektual seorang ulama terkemuka Nusantara, Abdul Qadir al-Mandili (1329–1385 H / 1910–1965 M), yang kontribusinya dalam bidang studi hadis terwujud melalui karya monumentalnya, Tuhfah al-Qāri’. Karya ini merepresentasikan sintesis penting antara pendekatan tradisional dan kontekstual dalam memahami hadis. Studi ini bertujuan untuk menganalisis karakteristik khas karya tersebut, kerangka metodologinya, serta pengaruhnya terhadap perkembangan tradisi intelektual Islam di kawasan Nusantara. Melalui analisis isi dan pendekatan historis, penelitian ini menemukan bahwa Tuhfah al-Qāri’ memberikan panduan praktis bagi umat Islam dalam memahami dan mengaplikasikan hadis yang selaras dengan realitas sosial dan budaya masyarakat lokal. Selain itu, karya ini mencerminkan kemampuan adaptif ulama Nusantara yang tetap berakar pada khazanah keilmuan Islam klasik, sembari merespons tantangan zaman mereka. Temuan ini menegaskan bahwa Tuhfah al-Qāri’ tidak hanya menjadi referensi penting dalam studi hadis, tetapi juga berfungsi sebagai jembatan intelektual antara khazanah keilmuan Islam global dan wacana keagamaan lokal, sehingga memperkaya kontinuitas dinamis pemikiran Islam di kawasan ini.]